Development of Mini Hydroponic Teaching Modules to Improve Critical Thinking Skills in Early Childhood - Supriati; Nita Priyanti (Journal of Childhood Development, 2024)
Hydroponics is a farming activity without soil which has an important role in building critical thinking skills for young children.  The role of mini hydroponics is outlined in the form of teaching modules which were developed to make it easier for teaching staff to present material to improve critical thinking skills for young children.  The aim of this research is to determine the development of mini hydroponic teaching modules in improving the critical thinking skills of young children and to analyze the feasibility of mini hydroponic teaching modules.  This research uses research & development methods with product development in the educational sector and uses a qualitative approach and is carried out at the Carsa Kids Tarakan Kindergarten from November 2023 to February 2024. The results of the research show that this mini hydroponic teaching module is suitable for use to improve thinking skills.  critical for young children.  The feasibility of this teaching module product is generated from validation scores from experts such as material experts, media experts and also language experts and critical thinking material experts.  This ajat module could be an alternative material for young children to improve their critical thinking skills.